Glucose kinetics during prolonged exercise in highly trained human subjects: effect of glucose ingestion - Jeukendrup, A. E.; Raben, A.; Gijsen, A.; Stegen, J. H.; Brouns, F.; Saris, W. H.; Wagenmakers, A. J. (The Journal of Physiology, 1999)
The objectives of this study were (1) to investigate whether glucose ingestion during prolonged exercise reduces whole body muscle glycogen oxidation, (2) to determine the extent to which glucose disappearing from the plasma is oxidized during exercise with and without carbohydrate ingestion and (3) to obtain an estimate of gluconeogenesis. After an overnight fast, six well-trained cyclists exercised on three occasions for 120 min on a bicycle ergometer at 50 % maximum velocity of O2 uptake and ingested either water (Fast), or a 4 % glucose solution (Lo-Glu) or a 22 % glucose solution (Hi-Glu) during exercise. Dual tracer infusion of [U-13C]-glucose and [6,6-2H2]-glucose was given to measure the rate of appearance (Ra) of glucose, muscle glycogen oxidation, glucose carbon recycling, metabolic clearance rate (MCR) and non-oxidative disposal of glucose. Glucose ingestion markedly increased total Ra especially with Hi-Glu. After 120 min Ra and rate of disappearance (Rd) of glucose were 51-52 µmol kg-1 min-1 during Fast, 73-74 µmol kg-1 min-1 during Lo-Glu and 117-119 µmol kg-1 min-1 during Hi-Glu. The percentage of Rd oxidized was between 96 and 100 % in all trials. Glycogen oxidation during exercise was not reduced by glucose ingestion. The vast majority of glucose disappearing from the plasma is oxidized and MCR increased markedly with glucose ingestion. Glucose carbon recycling was minimal suggesting that gluconeogenesis in these conditions is negligible.